2018
DOI: 10.2147/tcrm.s186347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dapagliflozin on serum uric acid levels in hospitalized type 2 diabetic patients with inadequate glycemic control: a randomized controlled trial

Abstract: BackgroundRaised serum uric acid (SUA) level is commonly observed in patients with type 2 diabetes mellitus (T2DM) and is associated with increased morbidity and mortality. Sodium-glucose cotransporter 2 inhibitor, a novel oral diabetic drug, might exert a potential hypouricemic effect. We evaluated the effects of dapagliflozin on SUA levels in hospitalized T2DM patients with inadequate glycemic control.MethodsIn this randomized controlled trial, 59 T2DM hospitalized patients with inadequate glycemic control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…9 Similar results were observed in a randomized control study conducted in china, which showed dapagliflozin effectively reduced serum uric acid level of hospitalized patients having inadequate glycemic control. 10 Both these results are consistent with finding of our study, as significant reduction in uric acid as well as HbA1c were observed when total population is concerned includes both dapagliflozin and canagliflozin groups. It can be said SGLT2 inhibitors as a whole has a decremental effect on serum uric acid, apart from the drugs used in our study, another molecule in this class i.e., empagliflozin also showed similar effect on serum uric acid as well as blood pressure of diabetic population.…”
Section: Discussionsupporting
confidence: 93%
“…9 Similar results were observed in a randomized control study conducted in china, which showed dapagliflozin effectively reduced serum uric acid level of hospitalized patients having inadequate glycemic control. 10 Both these results are consistent with finding of our study, as significant reduction in uric acid as well as HbA1c were observed when total population is concerned includes both dapagliflozin and canagliflozin groups. It can be said SGLT2 inhibitors as a whole has a decremental effect on serum uric acid, apart from the drugs used in our study, another molecule in this class i.e., empagliflozin also showed similar effect on serum uric acid as well as blood pressure of diabetic population.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the EMPA-REG OUTCOME trial (8,9) and the CANVAS program (14,15) reported that the beneficial effects of SGLT2 inhibitors on the eGFR occurred concomitantly with glycemic improvements. The reduction in the UA levels was also observed concurrently with the improvement in the glucose metabolism following SGLT2 inhibitor administration (28)(29)(30)(31)(32). These results suggest that the renal benefits of SGLT2 inhibitors are involved in the changes in several parameters, including UA levels and glucose metabolism.…”
Section: Discussionmentioning
confidence: 59%
“…Firstly, we do not analyze whether oral hypoglycemic agents have an effect on SUA. Sodium-glucose co-transporter 2 inhibitor (SGLT-2i) could improve glycemic control and lower SUA levels in T2DM (Hao et al, 2018). However, other hypoglycemic drugs, including metformin, rosiglitazone, glibenclamide, and pharmacologic insulin, do not have a large impact on SUA concentration (Hussain et al, 2018; Iliadis et al, 2007; MacFarlane, Liu & Solomon, 2015).…”
Section: Discussionmentioning
confidence: 99%